The current energy scenario and prospects of alternative, renewable energy sources in Malaysia / Nowshad Amin and Shahrul Anizan - Amin, Nowshad; Anizan, Shahrul (2006)
Malaysia is committed to become a developed nation by the year 2020 Energy is one of the important aspects to he considered in the development of a nation. Nowadays the crude oil price is increasing rapidly since past few years and it is not a good practice if Malaysia has been only depending on fossil fuel to generate electricity. To date, Malaysia has been generating energy using coal, natural gas, crude oil and hydro. A percentile amount of 47% of the energy generation uses crude oil. Total dependence on fossil fuel is not a healthy symptom on economic aspect. One of the ways to divert the dependence is to use the alternative and renewable energy resources. Since the 8th Malaysian Plan Malaysian Government has been focusing to apply renewable energy as their fifth energy source. Agriculture is one of Malaysian economic resources that produce municipal waste during the process. This wastage along with the municipal garbage can be used and converted into electrical energy which is called biomass energy. Malaysia is geographically closer to the equator, and has a big potential in manipulating solar energy as one of potential source of electrical energy. Malaysia receives 8 hours of sunshine per day with a possible average amount of 4.5 KWh electricity conversions. As renewable energy sources like solar panels are approaching toward affordable range, Malaysia should start using this sort of alternative and renewable energy as one of their alternatives of energy. This paper will show the current energy scenario of the world together with some introduction on prospective renewable energy source such as Solar Cell activities to promote Solar Panels to be the best suited renewable for Malaysia.